RANCANG BANGUN SISTEM INFORMASI PENDATAAN INVENTARIS BERBASIS WEB PADA SERVER PT JASA MARGA (PERSERO) TBK. CABANG PALIKANCI - nur syarief abdullah; Arif Rinaldi Dikananda; Saeful Anwar; Odi Nurdiawan (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
PT Jasa Marga (Persero) Tbk. The Palikanci branch is a toll gate support company, but computer Inventory Data Collection which includes servers and is still considered manual data collection so that it consumes a lot of paper and is very vulnerable to being lost and takes a lot of time to collect lost or torn data. To emphasize and learn in understanding the problems as described, the formulation of the problem that researchers can explain is to design a computerized information system for data collection of Jasa Marga's server inventory, create a database for data collection of server inventory items for managers to carry out their work. The purpose of the research is to find out, develop and create an ongoing asset collection application system into the PHP and HTML programming language using the MySQL database. So that researchers can draw conclusions in processing inventory data collection server by implementing applications that have been designed and built in a systematic and structured manner, so that the level of damage in the process of carrying out data collection for seafarers can be resolved.